Bioprosthetic mitral valve replacement in patients aged 65 years or younger: long-term outcomes with the Carpentier–Edwards PERIMOUNT pericardial valve. (12th February 2018) - Bourguignon, Thierry; Espitalier, Fabien; Pantaleon, Clémence; Vermes, Emmanuelle; El-Arid, Jean Marc; Loardi, Claudia; Karam, Elias; Candolfi, Pascal; Ivanes, Fabrice; Aupart, Michel
Abstract: OBJECTIVES: Mitral valve replacement using a bioprosthesis remains controversial in young patients because data on long-term outcomes are missing. This study evaluated the long-term results of the PERIMOUNT pericardial mitral bioprosthesis in patients aged 65 years or younger. METHODS: From 1984 to 2010, 148 Carpentier–Edwards PERIMOUNT mitral bioprostheses were implanted in 148 patients aged 65 years or younger. Baseline clinical, perioperative and follow-up data were recorded prospectively. Structural valve deterioration (SVD) was defined by strict echocardiographic assessment. RESULTS: The mean follow-up period was 8.6 ± 5.5 years, for a total of 1269 valve-years. Operative mortality rate was 2.0%. Fifty-one late deaths occurred (linearized rate 4.0% per valve-year). Actuarial survival rates averaged 70 ± 4%, 53 ± 6% and 31 ± 7% after 10, 15 and 20 years of follow-up, respectively. Actuarial freedom from SVD at 10, 15 and 20 years was 78 ± 5%, 47 ± 7% and 19 ± 7%, respectively. Reoperation was associated with no operative mortality. Actuarial freedom from reoperation due to SVD at 10, 15 and 20 years was 82 ± 4%, 50 ± 6% and 25 ± 8%, respectively. Competing risk analysis demonstrated an actual risk of explantation secondary to SVD at 20 years of 44 ± 5%. Expected valve durability was 14.2 years for this age group. CONCLUSIONS: In the selected patients aged 65 years or younger undergoing mitral valve replacement with a pericardial bioprosthesis, the expected valve durability was 14.2 years. Reoperation for SVD was associated with a low risk of mortality.